Measurement of J / ψ and ψ (2S) polarization in pp̄ collisions at √s = 1.8 TeV - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amendolia, SR; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Asakawa, T; et al. (2000)
We have measured the polarization of J/ψ and ψ(2S) mesons produced in pp̄ collisions at √s = 1.8 TeV, using data collected at the Collider Detector at Fermilab during 1992-1995. The polarization of promptly produced J/ψ [ψ(2S)] mesons is isolated from those produced in B-hadron decay, and measured over the kinematic range 4 [5.5] < PT < 20 GeV/c and |y| < 0.6. For PT ≳ 12 GeV/c we do not observe significant polarization in the prompt component. © 2000 The American Physical Society.